Preparation method and application of a sodium ion battery polyanion positive electrode material
Patent Information
- Application Number
- CN202611186751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]以上专利及现有技术制备的钠离子电池正极材料,因其导电性差、能量密度低和库仑效率低等缺陷限制了其发展
[0027] This invention discloses a method for preparing a polyanion cathode material for sodium-ion batteries and its application. Compared with the prior art, this invention has the following significant advantages:
Smart Images

Figure CN122931004A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a method for preparing and applying a polyanion cathode material for sodium-ion batteries. Background Technology
[0002] Sodium-ion batteries are attracting increasing attention due to their abundant resources, low cost, similar electrochemical performance to lithium-ion batteries, smaller size compared to other new types of batteries, reduced structural damage to materials during charging and discharging, and better cycle performance.
[0003] Chinese patent CN116825981A discloses a sodium-ion battery polyanion cathode material / C composite material and its preparation method. The preparation method includes steps such as preparation of precursor powder, control of precursor powder particle size, and secondary coating of polyanion cathode material.
[0004] Chinese Patent CN117712334A discloses a boric acid / carbon co-coated sodium-ion battery polyanion cathode material and its preparation method and application. The preparation method includes the following steps: (1) mixing sodium source, transition metal source, anion source and solid carbon source evenly and drying to obtain precursor powder; (2) mixing precursor powder with boric acid evenly and sintering in a non-oxidizing atmosphere to obtain sodium-ion battery polyanion cathode material.
[0005] Chinese patent CN117525391A discloses a polyanion cathode material for sodium-ion batteries and its preparation method. Potassium and ruthenium ions are simultaneously doped into the sodium iron phosphate pyrophosphate material, and carbon is coated onto the outer layer of the sodium iron phosphate pyrophosphate material.
[0006] The development of sodium-ion battery cathode materials prepared by the above patents and existing technologies is limited by their poor conductivity, low energy density and low coulombic efficiency. Summary of the Invention
[0007] To address the aforementioned problems, this invention provides a method for preparing and applying a polyanion cathode material for sodium-ion batteries, the operation steps of which are as follows:
[0008] S1: Add 17-22 parts sodium acetate, 0.1-1 parts manganese acetate, 8-12 parts citric acid, and 5-10 parts tetrabutyl titanate to 30-40 parts ethanol, stir and mix evenly to obtain solution 1;
[0009] S2: Add 1-5 parts of ammonium dihydrogen phosphate to 5-10 parts of deionized water, stir and mix to obtain solution 2;
[0010] S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture;
[0011] S4: Mix 26-40 parts of the mixture, 1-5 parts of the conductive material, and 1-5 parts of the modified graphene oxide, and then ball mill them to obtain the active material;
[0012] S5: Mix 55-63 parts of active material, 10-18 parts of conductive material, 3-9 parts of polytetrafluoroethylene, and 1-5 parts of isopropanol evenly, then coat the mixture onto the surface of a stainless steel mesh and dry it to obtain a sodium-ion battery polyanion cathode material.
[0013] S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
[0014] The high-temperature calcination temperature is 550-650℃, and the time is 200-240 minutes.
[0015] The ball-to-material mass ratio in the ball mill is 8-10:1, the ball mill speed is 400-500 r / min, and the ball milling time is 200-240 min.
[0016] The conductive material is one of carbon nanotubes, SuperP, acetylene black, carbon nanotubes, and Ketjen black.
[0017] The negative electrode is metallic sodium.
[0018] The diaphragm is made of glass fiber.
[0019] The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
[0020] The method for preparing the modified graphene oxide is as follows:
[0021] Synthesis and preliminary reaction of T1 complex intermediate: According to the mass ratio, add 10-15 parts of vinyl polyoxyethylene ether, 5-10 parts of hydrogen-containing silicone oil, 0.05-0.4 parts of 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane, and 1000-1200 parts of toluene to a reactor, stir evenly, then add 0.01-0.05 parts of chloroplatinic acid catalyst, heat to 80-90℃ to carry out hydrosilylation reaction, and continue stirring for 4-6 hours;
[0022] T2: Add 110-130 parts of graphene oxide, stir at 85-95℃ for 45-75 minutes, and then disperse by ultrasonication at 80-120W for 20-40 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation and washing, vacuum dry at 55-65℃ for 10-14 hours to obtain modified graphene oxide.
[0023] Reaction mechanism
[0024] Hydrosilylation reaction (T1): Vinyl polyoxyethylene ether and hydrogen-containing silicone oil undergo hydrosilylation under the action of a catalyst to generate a siloxane intermediate containing polyether segments (such as the Si-O-PEG structure). 2-Vinyl-5,5-dimethyl-1,3,2-dioxoborane acts as a crosslinking agent, introducing reactive sites through the boron-oxygen ring structure, thereby enhancing the binding ability of the intermediate with graphene oxide.
[0025] Graphene oxide modification (T2): The hydroxyl groups (-OH) on the surface of graphene oxide and the siloxane groups (-Si-O-) in the intermediate form covalent bonds (Si-OC) through a condensation reaction. At the same time, the boron oxide ring coordinates with the hydroxyl groups, stabilizing the interfacial structure. The hydrophilicity of the polyether segment (PEG) improves the dispersibility of graphene oxide in polar solvents, while inhibiting its π-π stacking and avoiding aggregation.
[0026] Technical effect
[0027] This invention discloses a method for preparing a polyanion cathode material for sodium-ion batteries and its application. Compared with the prior art, this invention has the following significant advantages:
[0028] 1. Significantly improves the electronic conductivity of polyanion cathode materials, thereby enhancing the rate performance of the battery.
[0029] 2. It enhances the cycle stability of the cathode material and extends the battery's lifespan.
[0030] 3. It improves the dispersibility and processing performance of graphene oxide, which is beneficial for large-scale industrial production. Attached Figure Description
[0031] Figure 1 This is a scanning electron microscope image of Example 3. Detailed Implementation
[0032] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the following detailed description is provided in conjunction with embodiments and comparative examples:
[0033] Electrochemical performance testing: Performed on the LANHE battery testing system, with a voltage range of 1.5-4.2V. Measurements were taken using constant current intermittent titration, with a charge / discharge current of 10mA / g for 10 minutes, followed by a 60-minute relaxation period. Specific capacity was measured at -30°C and 0.2C, and capacity retention was measured after 1000 cycles at 1C.
[0034] Example 1
[0035] A method for preparing and applying a polyanion cathode material for sodium-ion batteries, comprising the following steps:
[0036] S1: Add 17g sodium acetate, 0.1g manganese acetate, 8g citric acid, and 5g tetrabutyl titanate to 30g ethanol, stir and mix evenly to obtain solution 1;
[0037] S2: Add 1g of ammonium dihydrogen phosphate to 5g of deionized water, stir and mix to obtain solution 2;
[0038] S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture;
[0039] S4: Mix 26g of the mixture, 1g of the conductive material, and 1g of the modified graphene oxide, and then ball mill them to obtain the active material;
[0040] S5: Mix 55g of active material, 10g of conductive material, 3g of polytetrafluoroethylene and 1g of isopropanol evenly, coat the mixture onto the surface of a stainless steel mesh and dry it to obtain a sodium-ion battery polyanion cathode material.
[0041] S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
[0042] The high-temperature calcination temperature is 550℃ and the time is 200min.
[0043] The ball-to-material mass ratio in the ball mill is 8:1, the ball mill speed is 400 r / min, and the ball milling time is 200 min.
[0044] The conductive material is carbon nanotubes.
[0045] The negative electrode is metallic sodium.
[0046] The diaphragm is made of glass fiber.
[0047] The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
[0048] The method for preparing the modified graphene oxide is as follows:
[0049] Synthesis and preliminary reaction of T1 complex intermediate: 10g vinyl polyoxyethylene ether, 5g hydrogen-containing silicone oil, 0.05g 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane and 1000g toluene were added to the reactor and stirred evenly. Then 0.01g chloroplatinic acid catalyst was added and the temperature was raised to 80℃ to carry out hydrosilylation reaction and stirred continuously for 4 hours.
[0050] T2: Add 110g of graphene oxide and stir at 85℃ for 45 minutes. Then, disperse by ultrasonication at 80W for 20 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation, washing, and vacuum drying at 55℃ for 10 hours, modified graphene oxide is obtained.
[0051] Example 2
[0052] A method for preparing and applying a polyanion cathode material for sodium-ion batteries, comprising the following steps:
[0053] S1: Add 18g sodium acetate, 0.5g manganese acetate, 9g citric acid, and 6g tetrabutyl titanate to 33g ethanol, stir and mix evenly to obtain solution 1;
[0054] S2: Add 2g of ammonium dihydrogen phosphate to 6g of deionized water, stir and mix to obtain solution 2;
[0055] S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture;
[0056] S4: Mix 30g of the mixture, 2g of the conductive material, and 2g of the modified graphene oxide, and then ball mill them to obtain the active material;
[0057] S5: Mix 58g of active material, 12g of conductive material, 5g of polytetrafluoroethylene and 2g of isopropanol evenly, coat the mixture onto the surface of a stainless steel mesh, and dry it to obtain the sodium-ion battery polyanion cathode material.
[0058] S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
[0059] The high-temperature calcination was carried out at a temperature of 580°C for 210 minutes.
[0060] The ball-to-material mass ratio in the ball mill is 9:1, the ball mill speed is 450 r / min, and the ball milling time is 210 min.
[0061] The conductive material is superP.
[0062] The negative electrode is metallic sodium.
[0063] The diaphragm is made of glass fiber.
[0064] The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
[0065] The method for preparing the modified graphene oxide is as follows:
[0066] Synthesis and preliminary reaction of T1 complex intermediate: 12g vinyl polyoxyethylene ether, 6g hydrogen-containing silicone oil, 0.2g 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane and 1050g toluene were added to the reactor and stirred evenly. Then 0.02g chloroplatinic acid catalyst was added and the temperature was raised to 85℃ to carry out hydrosilylation reaction and stirred continuously for 5 hours.
[0067] T2: Add 115g of graphene oxide, stir at 88℃ for 55 minutes, and then disperse by ultrasonication at 90W for 25 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation, washing, and vacuum drying at 58℃ for 11 hours, modified graphene oxide is obtained.
[0068] Example 3
[0069] A method for preparing and applying a polyanion cathode material for sodium-ion batteries, comprising the following steps:
[0070] S1: Add 20g sodium acetate, 0.8g manganese acetate, 11g citric acid, and 8g tetrabutyl titanate to 38g ethanol, stir and mix evenly to obtain solution 1;
[0071] S2: Add 4g of ammonium dihydrogen phosphate to 8g of deionized water, stir and mix to obtain solution 2;
[0072] S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture;
[0073] S4: Mix 36g of the mixture, 4g of the conductive material, and 4g of the modified graphene oxide, and then ball mill them to obtain the active material;
[0074] S5: Mix 60g of active material, 16g of conductive material, 7g of polytetrafluoroethylene and 4g of isopropanol evenly, coat the mixture onto the surface of a stainless steel mesh and dry it to obtain a sodium-ion battery polyanion cathode material.
[0075] S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
[0076] The high-temperature calcination was carried out at a temperature of 630°C for 230 minutes.
[0077] The ball-to-material mass ratio in the ball mill is 9:1, the ball mill speed is 450 r / min, and the ball milling time is 230 min.
[0078] The conductive material is acetylene black.
[0079] The negative electrode is metallic sodium.
[0080] The diaphragm is made of glass fiber.
[0081] The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
[0082] The method for preparing the modified graphene oxide is as follows:
[0083] Synthesis and preliminary reaction of T1 complex intermediate: 14g of vinyl polyoxyethylene ether, 8g of hydrogen-containing silicone oil, 0.3g of 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane and 1150g of toluene were added to the reactor and stirred evenly. Then, 0.04g of chloroplatinic acid catalyst was added and the temperature was raised to 85℃ to carry out the hydrosilylation reaction. The mixture was stirred continuously for 5 hours.
[0084] T2: Add 125g of graphene oxide and stir at 93℃ for 65 minutes. Then, disperse by ultrasonication at 110W for 35 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation, washing, and vacuum drying at 63℃ for 13 hours, modified graphene oxide is obtained.
[0085] Example 4
[0086] A method for preparing and applying a polyanion cathode material for sodium-ion batteries, comprising the following steps:
[0087] S1: Add 22g sodium acetate, 1g manganese acetate, 12g citric acid, and 10g tetrabutyl titanate to 40g ethanol, stir and mix evenly to obtain solution 1;
[0088] S2: Add 5g of ammonium dihydrogen phosphate to 10g of deionized water, stir and mix to obtain solution 2;
[0089] S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture;
[0090] S4: Mix 40g of the mixture, 5g of the conductive material, and 5g of the modified graphene oxide, and then ball mill them to obtain the active material;
[0091] S5: Mix 63g of active material, 18g of conductive material, 9g of polytetrafluoroethylene and 5g of isopropanol evenly, coat the mixture onto the surface of a stainless steel mesh and dry it to obtain a sodium-ion battery polyanion cathode material.
[0092] S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
[0093] The high-temperature calcination was carried out at a temperature of 650°C for 240 minutes.
[0094] The ball-to-material mass ratio in the ball mill is 10:1, the ball mill speed is 500 r / min, and the ball milling time is 240 min.
[0095] The conductive material is Ketjen Black.
[0096] The negative electrode is metallic sodium.
[0097] The diaphragm is made of glass fiber.
[0098] The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
[0099] The method for preparing the modified graphene oxide is as follows:
[0100] Synthesis and preliminary reaction of T1 complex intermediate: 15g vinyl polyoxyethylene ether, 10g hydrogen-containing silicone oil, 0.4g 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane and 1200g toluene were added to the reactor and stirred evenly. Then 0.05g chloroplatinic acid catalyst was added and the temperature was raised to 90℃ to carry out hydrosilylation reaction and stirred continuously for 6 hours.
[0101] T2: Add 130g of graphene oxide and stir at 95℃ for 75 minutes. Then, disperse by ultrasonication at 120W for 40 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation, washing, and vacuum drying at 65℃ for 14 hours, modified graphene oxide is obtained.
[0102] Comparative Example 1
[0103] No modification was made to the graphene oxide; otherwise, it was the same as in Example 1.
[0104] Comparative Example 2
[0105] No hydrogen-containing silicone oil was added; otherwise, it was the same as in Example 1.
[0106] Comparative Example 3
[0107] The same as in Example 1 was used, but without the addition of 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane.
[0108] Specific capacity / mA·h / g Specific capacity retention rate / % Example 1 113.8 91.8 Example 2 115.6 92.6 Example 3 119.3 94.2 Example 4 121.5 94.9 Comparative Example 1 83.7 73.1 Comparative Example 2 96.1 85.2 Comparative Example 3 103.2 86.6
[0109] Based on the data analysis of the above embodiments and comparative examples, the sodium-ion battery polyanion cathode material prepared by the present invention also exhibits excellent specific capacity and rate performance at low temperatures.
[0110] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing and applying a polyanion cathode material for sodium-ion batteries, comprising the following steps: S1: Add 17-22 parts sodium acetate, 0.1-1 parts manganese acetate, 8-12 parts citric acid, and 5-10 parts tetrabutyl titanate to 30-40 parts ethanol, stir and mix evenly to obtain solution 1; S2: Add 1-5 parts of ammonium dihydrogen phosphate to 5-10 parts of deionized water, stir and mix to obtain solution 2; S3: After mixing solution 1 and solution 2 evenly, dry them, then calcine them at high temperature under an argon atmosphere, and then cool them to room temperature to obtain a mixture; S4: Mix 26-40 parts of the mixture, 1-5 parts of the conductive material, and 1-5 parts of the modified graphene oxide, and then ball mill them to obtain the active material; S5: Mix 55-63 parts of active material, 10-18 parts of conductive material, 3-9 parts of polytetrafluoroethylene, and 1-5 parts of isopropanol evenly, then coat the mixture onto the surface of a stainless steel mesh and dry it to obtain a sodium-ion battery polyanion cathode material. S6: Sodium-ion battery is assembled by using polyanion cathode material as the cathode, along with the anode, separator, and electrolyte.
2. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The high-temperature calcination temperature is 550-650℃, and the time is 200-240 minutes.
3. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The ball-to-material mass ratio in the ball mill is 8-10:1, the ball mill speed is 400-500 r / min, and the ball milling time is 200-240 min.
4. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The conductive material is one of carbon nanotubes, SuperP, acetylene black, carbon nanotubes, and Ketjen black.
5. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The negative electrode is metallic sodium.
6. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The diaphragm is made of glass fiber.
7. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The electrolyte is a mixed solution formed by dissolving 1 mol / L sodium perchlorate in ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and adding 5% fluoroethylene carbonate.
8. The preparation method and application of a sodium-ion battery polyanion cathode material according to claim 1, characterized in that: The method for preparing the modified graphene oxide is as follows: Synthesis and preliminary reaction of T1 complex intermediate: According to the mass ratio, add 10-15 parts of vinyl polyoxyethylene ether, 5-10 parts of hydrogen-containing silicone oil, 0.05-0.4 parts of 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane, and 1000-1200 parts of toluene to a reactor, stir evenly, then add 0.01-0.05 parts of chloroplatinic acid catalyst, heat to 80-90℃ to carry out hydrosilylation reaction, and continue stirring for 4-6 hours; T2: Add 110-130 parts of graphene oxide, stir at 85-95℃ for 45-75 minutes, and then disperse by ultrasonication at 80-120W for 20-40 minutes to allow the intermediate to fully react with the hydroxyl groups on the surface of graphene oxide. After centrifugation and washing, vacuum dry at 55-65℃ for 10-14 hours to obtain modified graphene oxide.
Citation Information
Patent Citations
Sodium ion battery polyanion positive electrode material / C composite material and preparation method thereof
CN116825981A
Sodium ion battery polyanion positive electrode material and preparation method thereof
CN117525391A
Boric acid / carbon co-coated sodium ion battery polyanion positive electrode material as well as preparation method and application thereof
CN117712334A